Pengembangan Lembar Kerja Peserta Didik Berbasis Inkuiri Terbimbing pada Materi Sistem Pencernaan Kelas XI SMA - Askar, Asriani; Daud, Firdaus; Syamsiah, Syamsiah (Universitas Negeri Makassar, 2019)
Abstract. This research is aimed to produce a Student Worksheet based Guided Inquiry on Digestive System material for class XI senior high school that is valid and practical. The type of this research is research and development (R & D). The development of this student worksheet used ADDIE models. The stages of ADDIE are Analyze, Design, Develop, Implement and Evaluate . The evaluation of this student worksheet is evaluated by two expert validators. The validity product of student worksheet based guided inquiry is obtained from expert validators with a validity score of 4,11 (valid). The practicality of the product is obtained from teachers response with a practicality score of 89.75 (very practical) and students response with a practicality score of 86.0075 (very practical). Based on the results, it can be concluded that the development of student worksheet based Guided Inquiry on Digestive System material for class XI senior high school is valid and practical. Keywords: Student worksheet, Guided Inquiry, Valid, Practical.